2007
DOI: 10.12930/0271-9517-27.2.50
|View full text |Cite
|
Sign up to set email alerts
|

Adding Insight to Intrusive Advising and Its Effectiveness with Students on Probation

Abstract: In this study, I examined the effectiveness of adding insight-oriented strategies to an intrusive academic-advising approach with students on academic probation. Twenty males and 22 females at a comprehensive private university participated in the study. Students who attended three to eight meetings had a significant improvement in semester GPA compared to students who attended one or two meetings or no meetings. This study suggests that insight-oriented intrusive advising had a positive affect on academic ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…Once this pattern has been established, the advisor and student can begin to develop a plan that addresses issues that are specifically distracting the student from reaching and completing his or her educational goals. (Vander Schee, 2007). Simon, Tovar and Edson (2003) conceptualized and pilot tested their "re-orientation" (p. 553) on probationary students by incorporating and monitoring a student's academic difficulties through intrusive advisement.…”
Section: Intrusive Advisementmentioning
confidence: 99%
See 4 more Smart Citations
“…Once this pattern has been established, the advisor and student can begin to develop a plan that addresses issues that are specifically distracting the student from reaching and completing his or her educational goals. (Vander Schee, 2007). Simon, Tovar and Edson (2003) conceptualized and pilot tested their "re-orientation" (p. 553) on probationary students by incorporating and monitoring a student's academic difficulties through intrusive advisement.…”
Section: Intrusive Advisementmentioning
confidence: 99%
“…The results of their re-orientation efforts indicated statistically significant higher motivation, a favorable attitude toward educators, an increase in verbal confidence, and an increase in receptivity to institutional assistance, personal counseling and social engagement on campus. The researchers suggested that a comprehensive approach to advising, such as insight-oriented intrusive advising, appears to be effective in increasing the academic achievement of students on academic probation (Tutty & Ratliff, 2012;Gordon, Habley, & Grites, 2008;Vander Schee 2007;Tovar & Simon, 2006;Braxton, Hirschy, McClendon, 2004;Hunter & White, 2004;Simon, Tovar & Edson, 2003;Kadar, 2001;Gordon & Steele, 1992;Crockett, 1985).…”
Section: Intrusive Advisementmentioning
confidence: 99%
See 3 more Smart Citations